PENDIDIKAN NILAI ANTI-BULLYING: GAGASAN PENGEMBANGAN INSTRUMEN PENILAIAN KARAKTER UNTUK PROGRAM SIPENALI - Rega Sukmawati; Basukiyatno, Basukiyatno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Bullying in elementary schools is a critical issue in education that has long-term effects on students' psychological, social, and moral development. Value education plays a vital role in shaping students’ character, fostering empathy, tolerance, responsibility, and self-control as essential foundations for preventing bullying behavior. This article proposes a conceptual framework for developing an anti-bullying character assessment instrument as part of value education evaluation within the SIPENALI Program (Anti- Bullying Prevention and Response System). This descriptive qualitative study is based on theoretical review and reflection on school-based practices. The proposed instrument consists of two main formats: a student attitude scale and a teacher observation rubric, covering six key value dimensions: empathy, tolerance, selfcontrol, responsibility, moral courage, and fairness. This design is expected to serve as a practical tool for teachers to systematically assess students’ character internalization and to support the sustainability of antibullying initiatives rooted in value education at the elementary level.